Interpretação em atrações turísticas patrimoniais: um modelo de planejamento. - Constantino Figueira, Michel (Museologia e Patrimônio, 2024)
Interpretation is one of the most effective technical tools in the tourism qualification process with a focus on heritage attractions. Its relevance tends to be a differentiator in the tourism development process with a focus on the interactive and sensorial association of visitors with goods and references, material and immaterial, symbolically representative of the past. Furthermore, interpretation, as an educational resource, aims to generate knowledge, awareness and conservation of heritage, consequently contributing to the projection of heritage tourism. This article presents an interpretative planning model for heritage tourist attractions, developed from systematic research on the topic "interpretation" in scientific articles from qualis 1 journals, in the areas of tourism and heritage. Based on the literature, this planning model was designed as an open and editable system, considering its applicability conditioned to the reality of each attraction. Theoretically, the proposed model is composed of descriptive data and tables of pragmatic categories (narratives, interactivity, thematization and complementary elements), including methods and resources considered potentially applicable in conducting efficient of interpretative planning. It is expected that it can contribute, theoretically, technically and scientifically, to future projects, studies and actions around the uses of interpretation to qualify the visitor's experience in heritage tourist attractions.